The Impact of ISO Standards Implementation on Employee Performance of Executive Level Employees in Colombo Dockyard PLC - Madhuranga, H.L.K.; Weerakkody, W.A.S. (Department of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, 2015)
Today the customers of any business in the competitive world expect products and services meeting highest standards. The rapid rate of globalization has enabled this expectation to reach almost all parts of the world. Therefore, today organizations have to provide products and services at the world class level. This level can be reached through the adoption and implementation of world class strategies. International organization for standardization (ISO) certification is one of those strategies for organizations to reach the world class level. And also these standards lead employees for higher performance. Higher performance of employees also very critical for organizations to survive in the contemporary world. Thus, this study will examine the relationship between ISO standards implementation and employee performance of executive level employees on Colombo Dockyard PLC. To accomplishment of objectives quantitative research method and questionnaire will be used in order to collect primary data. Sample will be 40 employees represent from the population and it will focus only for the executive level employees and SPSS data analysis software will be used accordingly. The research results can be used as a guideline for the organization to have better understanding of ISO standards implementation and furthermore it will help to implement ISO standards effectively to increase employee performance in the organization. As well as results can be used for the other companies who are trying to implement ISO standards.
Keywords: ISO Standards; ISO Certification; Employee Performance